2021
DOI: 10.2196/21795
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of General Practitioners Toward Prescription of Mobile Health Apps: Qualitative Study

Abstract: Background Mobile health (mHealth) apps are a potential means of empowering patients, especially in the case of multimorbidity, which complicates patients’ care needs. Previous studies have shown that general practitioners (GPs) have both expectations and concerns regarding patients’ use of mHealth apps that could impact their willingness to recommend the apps to patients. Objective The aim of this qualitative study is to investigate French GPs’ attitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 33 publications
2
77
2
Order By: Relevance
“…Contrary to our assumptions and previous research indicating data security concerns as a major barrier to using health apps [ 50 ], perceived threat to privacy had no significant influence on the acceptance of hypertension apps in our study. Potentially, the sample was already aware of certified disease management apps approved by statutory insurance companies and other trusted sources in Germany.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our assumptions and previous research indicating data security concerns as a major barrier to using health apps [ 50 ], perceived threat to privacy had no significant influence on the acceptance of hypertension apps in our study. Potentially, the sample was already aware of certified disease management apps approved by statutory insurance companies and other trusted sources in Germany.…”
Section: Discussioncontrasting
confidence: 99%
“…They identified 3 groups of attitudes. The first group corresponds to GPs very willing to prescribe mHealth apps and devices, with positive perceptions of (1) the benefits for patients and for clinical practice and (2) ease of use; the second group represents GPs worried about the protection of patient data and the reliability of mHealth app and device content; and the third group corresponds to GPs concerned about the implications of mHealth apps and devices for their clinical practice (additional working time, modification of the patient–physician relationship, and the importance of mHealth app and device certification by independent entities) [ 23 ]. Consistently, an Australian study showed that the perceived barriers of GPs to prescribing mHealth apps and devices were generational digital divide, a lack of knowledge and reliable resources listing prescriptible mHealth apps and devices, additional working time it may represent for GPs, and concerns about data security [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 51 Therefore, it is important to strengthen the digital training of older TCM doctors and TCM doctors with high titles. 52 Compared with the doctors from primary TCM hospitals, the doctors from comprehensive TCM hospitals had higher scores for convenience. In China, comprehensive TCM hospitals receive the most government investment.…”
Section: Discussionmentioning
confidence: 99%